2003
DOI: 10.1016/s0741-5214(03)00328-8
|View full text |Cite
|
Sign up to set email alerts
|

Blinded comparison of preoperative duplex ultrasound scanning and contrast arteriography for planning revascularization at the level of the tibia

Abstract: Findings at DU and CA typically agree when used to select tibial or peroneal arteries for bypass grafting. With DU there is occasional difficulty in identification of the peroneal artery, but selection of the actual artery used is accurate. Peak systolic velocity, end-diastolic velocity, and diameter characteristics correlate with arteriographic criteria for tibial bypass target artery selection. If DU enables adequate identification of a target artery for bypass grafting, and especially if the peroneal artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…16 High-quality DUS performed by well-trained vascular technologists or physicians may therefore represent a good alternative for patients in need of lower extremity revascularization even in cases of more complex and critical disease. This was supported by Grassbaugh et al, who compared preoperative DUS with DSA for planning of revascularization at the crural (tibial/ peroneal arterial) level 11 as well as more recently by n/a n/a Ihlberg et al 13 PAD, mainly Fontaine stage II 80-86% 97% n/a n/a n/a n/a…”
Section: Ability Of Dus In Defining Treatment Plansmentioning
confidence: 83%
See 2 more Smart Citations
“…16 High-quality DUS performed by well-trained vascular technologists or physicians may therefore represent a good alternative for patients in need of lower extremity revascularization even in cases of more complex and critical disease. This was supported by Grassbaugh et al, who compared preoperative DUS with DSA for planning of revascularization at the crural (tibial/ peroneal arterial) level 11 as well as more recently by n/a n/a Ihlberg et al 13 PAD, mainly Fontaine stage II 80-86% 97% n/a n/a n/a n/a…”
Section: Ability Of Dus In Defining Treatment Plansmentioning
confidence: 83%
“…3,4 The performance of DUS in the infrapopliteal runoff via the crural (tibial/peroneal arteries) and pedal vessels compared to DSA was analyzed separately in five selected citations. 11,12,16,18,21 This was most recently studied by the Joint Endovascular and Non-Invasive Assessment of LImb perfusion (JENALI) Group, which used a novel anatomical scoring system to compare its ability to detect patent or occluded vessels compared to DSA. 21 The highest accuracy was in the (more superficial) tibial arteries compared to the peroneal artery; data are summarized in Table 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, duplex ultrasonography (DA) has gained a major role in the pre-operative evaluation of patients undergoing lower extremity bypass (Ascher et al, 1999;Grassbaugh et al, 2003;Ligush et al, 1998;Pemberton et al, 1996;Proia et al, 2001). Mazzariol et al reported that the use of dupplex ultrasonography can provide enough information for surgery in more than 83% of patients with arterial stenosis and that an abnornal femoral artery waveform was 100% predictive for detecting stenosis greater than 80% (Mazzariol et al, 2000) Proia et al have also confirmed these results (Proia et al, 2001).…”
Section: Pre-operative Ultrasound Usementioning
confidence: 99%
“…1 Duplex ultrasonography (DUS) is a primary screening tool used to evaluate arterial disease in carotid arteries, renal arteries, and peripheral arteries. [2][3][4][5][6][7][8] It is also used as a surveillance tool in postintervention patients to monitor re-stenosis or to detect disease development in another location. 9-17 DUS is an optimal modality for these applications, as it is noninvasive and safe, with relatively no morbidity.…”
mentioning
confidence: 99%